(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The article discusses the features of audit and audits, the study and analysis of such features makes it possible to determine what place and what role audit occupies in the financial control system, as well as what makes it possible to identify audits in relation to various organizations and what measures need to be carried out in order to identify violations and eliminate them in the future.